What do we know about the future of poverty in relation to food systems? - Pauw, Karl; Dorosh, Paul A.; Xu, Wenqian; Balié, Jean (International Food Policy Research Institute, 2025)
Global poverty declined rapidly over the past 25 years, from around 30 percent to 8.5 percent today, but a series of global crises caused the pace of poverty reduction to slow down from 2020 onward. Some regions have done well; for instance, the East Asia and Pacific region has now effectively eliminated extreme poverty, a Sustainable Development Goal (SDG), while extreme poverty in South Asia is expected to be eradicated by 2030. But with almost no further reduction in the extreme poverty rate in sub-Saharan Africa until 2030, the number of poor people in this region will expand by 10 percent to reach 500 million. This means that by 2030, around 80 percent of the global population of poor people will live in sub-Saharan Africa.